Dynamics of Rye Chromosome 1R Regions with High or Low Crossover Frequency in Homology Search and Synapsis Development - Valenzuela, Nohelia T.; Perera, Esther; Naranjo, Tomás (PLOS ONE, 2012)
In many organisms, homologous pairing and synapsis depend on the meiotic recombination machinery that repairs double-strand DNA breaks (DSBs) produced at the onset of meiosis. The culmination of recombination via crossover gives rise to chiasmata, which locate distally in many plant species such as rye, Secale cereale. Although, synapsis initiates close to the chromosome ends, a direct effect of regions with high crossover frequency on partner identification and synapsis initiation has not been demonstrated. Here, we analyze the dynamics of distal and proximal regions of a rye chromosome introgressed into wheat to define their role on meiotic homology search and synapsis. We have used lines with a pair of two-armed chromosome 1R of rye, or a pair of telocentrics of its long arm (1RL), which were homozygous for the standard 1RL structure, homozygous for an inversion of 1RL that changes chiasma location from distal to proximal, or heterozygous for the inversion. Physical mapping of recombination produced in the ditelocentric heterozygote (1RL/1RLinv) showed that 70% of crossovers in the arm were confined to a terminal segment representing 10% of the 1RL length. The dynamics of the arms 1RL and 1RLinv during zygotene demonstrates that crossover-rich regions are more active in recognizing the homologous partner and developing synapsis than crossover-poor regions. When the crossover-rich regions are positioned in the vicinity of chromosome ends, their association is facilitated by telomere clustering; when they are positioned centrally in one of the two-armed chromosomes and distally in the homolog, their association is probably derived from chromosome elongation. On the other hand, chromosome movements that disassemble the bouquet may facilitate chromosome pairing correction by dissolution of improper chromosome associations. Taken together, these data support that repair of DSBs via crossover is essential in both the search of the homologous partner and consolidation of homologous synapsis.